INTEGRASI TEORI PEDAGOGIK DAN PSIKOLOGI PENDIDIKAN LANDASAN TEORI BAGI PENCIPTAAN KELAS YANG EFEKTIF - Suci Setianingrum; Nadia Permata Sari; Atika Aladawiyah; Juwita Hartini (Linggau Journal of Elementary School Education, 2026)
This study examines the relationship between pedagogical approaches and psychological aspects in supporting the effectiveness of the classroom learning process. The study was conducted using a qualitative approach through literature review utilizing various relevant scientific sources. Data were obtained from journals, books, and articles, then analyzed by reviewing and comparing various existing research findings. The results of the study indicate that learning success is influenced not only by the teaching strategies used, but also by the teacher's ability to understand the conditions and characteristics of students. The integration of pedagogy and educational psychology can create a more interactive learning atmosphere, increase student engagement, and strengthen the relationship between teachers and students. In addition, a comfortable learning environment and appropriate methods also support the creation of an effective classroom. Thus, the combination of these two approaches is a crucial factor in building more adaptive and meaningful learning.